Titanium-modified lithium silicate carbon dioxide capture material and method of preparation

CN122999131APending Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611298775.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了解决传统方法制备的Li4SiO4存在活性位点不足、吸附容量偏低的缺陷,本发明首次尝试了采用二元复配锂源,其利用不同锂盐的理化特性协同互补,调控Li4SiO4成相纯度与微观孔隙结构,提高了Li4SiO4基体的CO2活性

Benefits of technology

[0028]1、本发明所设计和制备钛改性硅酸锂复合材料,首次采用了碳酸锂与氢氧化锂复配锂源来制备出了高活性的Li4SiO4,并创新性引入Li2TiO3作为高活Li4SiO4的结构支撑材料。通过优化后,得到了性能最优的复合材料,其首次二氧化碳捕集容量为0.17 g CO2 /g吸附剂,循环20圈后,二氧化碳捕集容量还可为0.15 g CO2 /g 吸附剂,循环保持率为88.2%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999131A_ABST
    Figure CN122999131A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of environmental energy material preparation, and particularly relates to a titanium modified lithium silicate carbon dioxide capture material and a preparation method. The material comprises Li4SiO4 and Li2TiO3, wherein the high-activity Li4SiO4 material prepared by reacting a binary lithium source composed of lithium carbonate and lithium hydroxide with silicon dioxide is used for carbon dioxide capture, and the in-situ generated Li2TiO3 is used as a structural support material of the Li4SiO4, so as to further improve the stability of the Li4SiO4 in the repeated carbon dioxide capture process. The application solves the problems of the prior art lithium silicate-based carbon capture material, such as low adsorption capacity, easy attenuation and failure in the cycle process, and the like. The preparation method is simple and controllable, has low requirements on equipment, low energy consumption, simple steps, and the obtained product has superior performance, and is easy to be industrialized and applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental and energy materials preparation technology, specifically relating to a titanium-modified lithium silicate carbon dioxide capture material and its preparation method. Background Technology

[0002] Despite significant progress in various research areas within the energy system, the use of fossil fuels will not be completely replaced in the foreseeable future. The combustion of fossil fuels undoubtedly releases large amounts of CO2 into the atmosphere. Consequently, atmospheric carbon dioxide concentrations have been steadily increasing over the past few decades. The problem of excessive atmospheric carbon dioxide concentrations requires effective solutions, and CO2 capture and utilization (CCU) technology is considered one of the most promising technologies for achieving temperature targets. The CO2 capture process accounts for 70% of the total cost of the entire CCU process; therefore, front-end carbon capture is crucial for breakthroughs in CCU technology. Carbon capture provides a truly green source for subsequent carbon utilization. CCU technology can be used to reduce carbon dioxide emissions in industries with high CO2 emissions, such as steel and coal-fired power plants.

[0003] Common CO2 capture materials mainly include Li4SiO4, alkali metal oxide composites (CaO, MgO, etc.), amines, zeolites, MOFs, etc. However, in currently available literature, the initial carbon dioxide capture capacity of Li4SiO4 when adsorbing carbon dioxide is generally less than 0.15 g CO2 / g adsorbent. For example, in the paper "Kinetic and thermodynamic investigations on the cyclic CO2 adsorption-desorption processes of lithium orthosilicate", Li4SiO4 adsorbent was directly prepared by ball milling and mixing traditional lithium source Li2CO3 and SiO2 and solid-state sintering. The initial carbon dioxide capture capacity of the published product under optimized preparation and adsorption conditions (600 °C) was only 0.085 g CO2 / g adsorbent. Another example is "K2CO3 promoted novel Li4SiO4-based sorbents from sepiolite with high CO2 capture capacity under different CO2 partial pressures", which directly prepared potassium-modified Li4SiO4 adsorbent by solid-state sintering. The initial carbon dioxide capture capacity of the published product at 600 °C was only 0.139 g CO2 / g adsorbent. After 5 or more cycles, the carbon dioxide capture capacity is generally less than 0.10 g CO2 / g adsorbent. For example, in the paper "Li4SiO4 modification on the surface of amorphous silica porous body and CO2removal method characteristics", amorphous silica was used to modify Li4SiO4 adsorbent. After 20 cycles, the carbon dioxide capture capacity of the disclosed product at 600 °C was only 0.041 g CO2 / g adsorbent. In another example, in the paper "Synthesis and evaluation in the CO2 capture process of potassium-modifiedlithium silicates produced from steel metallurgical slags", slag was used to modify potassium-containing Li4SiO4 adsorbent. After 20 cycles, the carbon dioxide capture capacity of the disclosed product at 600 °C was only 0.015 g CO2 / g adsorbent. Summary of the Invention

[0004] To address the issues of low capacity and deactivation in CO2 capture cycles of lithium silicate and modified lithium silicate materials in existing technologies, this invention, for the first time, utilizes a lithium source composed of lithium carbonate and lithium hydroxide to prepare highly active Li4SiO4. Furthermore, it employs the combination of Li2TiO3 and Li4SiO4, and prepares a titanium-modified lithium silicate CO2 capture composite material with excellent CO2 capture cycle performance in sintering TiO2 and highly active Li4SiO4 in situ.

[0005] To address the shortcomings of traditional methods in preparing Li4SiO4, such as insufficient active sites and low adsorption capacity, this invention, for the first time, employs a binary composite lithium source. This utilizes the synergistic and complementary physicochemical properties of different lithium salts to regulate the phase purity and microporous structure of Li4SiO4, thereby improving the CO2 activity of the Li4SiO4 matrix. Simultaneously, Li2TiO3, due to its high melting point and strong anti-sintering ability, is suitable as a structural carrier for Li4SiO4 carbon capture materials. Based on this, an in-situ synthesis process is used to introduce TiO2 into the binary lithium source-modified Li4SiO4 system to synthesize titanium-modified lithium silicate CO2 capture materials. The high-activity Li4SiO4 prepared using the binary lithium source achieves an improvement in carbon capture capacity, while the in-situ formation of Li2TiO3 from TiO2 and Li4SiO4 further improves the cycling stability of the Li4SiO4 material.

[0006] The innovation of this invention lies in the first-time preparation of highly active Li4SiO4 using a binary lithium source of lithium carbonate and lithium hydroxide, and the in-situ introduction of Li2TiO3 as a structural support material for this Li4SiO4, further enhancing the stability of the material during repeated carbon dioxide capture. The prepared titanium-modified lithium silicate material effectively overcomes the technical shortcomings of traditional lithium silicate, such as low capacity and poor cycle stability, filling the gap in the application of high-performance composite modified Li4SiO4 materials in the field of carbon dioxide capture.

[0007] This invention discloses a titanium-modified lithium silicate composite material, wherein the composite material comprises Li2TiO3 and Li4SiO4; the composite material is obtained by calcining a mixture of Li4SiO4 precursor, SiO2 and TiO2; and the mass ratio of Li4SiO4 to Li2TiO3 in the composite material is 7-9:1-3.

[0008] As a preferred embodiment, the present invention discloses a titanium-modified lithium silicate composite material in which the selected Li4SiO4 precursor is a binary lithium source formed by the compounding of lithium carbonate and lithium hydroxide, wherein the mass ratio of lithium carbonate to lithium hydroxide is 7.8-8.2:1.8-2.2, preferably 8:2. The preferred mass ratio of lithium carbonate to lithium hydroxide is controlled at 7.8-8.2:1.8-2.2 because lithium hydroxide has higher reactivity, which can promote the lithium-silicon solid-phase reaction during calcination, reduce the activation energy, and facilitate the formation of a well-crystallized Li4SiO4 active phase. Simultaneously, lithium carbonate has good thermal stability, which can inhibit excessive sintering and particle agglomeration of the precursor at high temperatures. The synergistic combination of the two achieves the preparation of highly active lithium silicate. Excessive use of lithium hydroxide will lead to increased high-temperature volatilization of the lithium source, making the material prone to severe sintering and causing a decrease in the specific surface area of ​​the material. Insufficient use of lithium hydroxide will result in insufficient driving force for the lithium-silicon solid-phase reaction, incomplete reaction, reduced formation of the Li4SiO4 active phase, and ultimately a significant decrease in the carbon dioxide capture capacity of the material.

[0009] As a preferred embodiment, the mass ratio of Li4SiO4 precursor, SiO2 and TiO2 is: Li4SiO4 precursor:SiO2:TiO2 = 5.5-6.5:1.7-2.3:1.2-2.8. This invention controls the mass ratio of Li4SiO4 precursor, SiO2, and TiO2 to Li4SiO4 precursor:SiO2:TiO2 = 5.5-6.5:1.7-2.3:1.2-2.8, and more preferably 6:2:2. This feeding ratio allows for the formation of the target phase composition after calcination, generating a sufficient amount of Li4SiO4 active phase while simultaneously generating an appropriate amount of Li2TiO3 structural support phase in situ. This ensures the material has a high carbon dioxide capture capacity and also helps to inhibit particle sintering and agglomeration during high-temperature cycling by utilizing the framework effect of Li2TiO3, thus achieving a synergistic improvement in adsorption capacity and cycling stability. If the amount of titanium dioxide is too high, it will lead to the generation of excessive Li2TiO3 and insufficient Li4SiO4 active component, resulting in a significant decrease in the overall carbon dioxide capture capacity of the composite material. If the amount of titanium dioxide is too low, it will lead to insufficient content of the Li2TiO3 support phase generated in the reaction, making it difficult to exert the framework isolation and anti-sintering effects, resulting in accelerated capacity decay and poor stability during cycling.

[0010] This invention discloses a titanium-modified lithium silicate composite material, with a preferred calcination temperature of 700-950 °C. More preferably, it is 820-900 °C.

[0011] This invention relates to a titanium-modified lithium silicate composite material, which is calcined for 1-3 hours.

[0012] The present invention discloses a method for preparing a titanium-modified lithium silicate composite material, comprising the following steps:

[0013] Raw materials are taken according to the design group allocation ratio, mixed evenly, and calcined at 700-950 ℃, preferably 820-900 ℃, to obtain the product; the raw materials include Li4SiO4 precursor, SiO2 and TiO2.

[0014] In this invention, the raw material TiO2 is rutile phase TiO2, and Li2TiO3 is generated in situ by the reaction of sintered TiO2 with Li4SiO4.

[0015] As a preferred embodiment, the present invention provides a method for preparing a titanium-modified lithium silicate composite material, which involves uniformly mixing by ball milling, with the ball milling speed controlled at 600-800 r / min, the ball milling time at 4-8 h, and the ball-to-material mass ratio at 8:1.

[0016] As a preferred embodiment, the preparation method of the titanium-modified lithium silicate composite material of the present invention involves calcination for 1-3 hours.

[0017] Preferably, the present invention provides a method for preparing a titanium-modified lithium silicate composite material, wherein the TiO2 used includes commercially available TiO2 with a particle size of less than or equal to 20 nm.

[0018] Preferably, the present invention provides a method for preparing a titanium-modified lithium silicate composite material, wherein the SiO2 used includes commercially available SiO2 with a particle size of less than or equal to 50 nm.

[0019] This invention discloses a method for preparing a titanium-modified lithium silicate composite material, wherein the mass ratio of the prepared Li4SiO4 to Li2TiO3 in the composite material is 7-9:3-1, preferably 7.5-8.5:1.5-2.5.

[0020] As a preferred embodiment, the present invention uses a binary lithium source precursor composed of lithium carbonate and lithium hydroxide, SiO2 and TiO2, which are ball-milled and mixed, followed by high-temperature sintering to obtain a Li4SiO4-20%H-Ti composite material; wherein...

[0021] As a preferred option, the ball milling conditions are: rotation speed 800 r / min, ball milling time 6 h, and ball-to-material mass ratio 8:1.

[0022] Preferably, the high-temperature sintering temperature is 880~900 ℃, and the sintering procedure is as follows: a heating rate of 5 ℃ / min from 0-500 ℃; a heating rate of 10 ℃ / min from 500-800 ℃; and a heating rate of 5 ℃ / min from 800-900 ℃. After reaching the set high-temperature sintering temperature, the temperature is held for 2 h. After high-temperature sintering, the mass ratio of Li4SiO4 to Li2TiO3 is 8:2. Under this scheme, the product's cycle performance and the total carbon dioxide absorption during 20 cycles are both higher than other schemes.

[0023] The titanium-modified lithium silicate composite material obtained in this invention is first activated by heating from room temperature to 850 °C and holding for 5 min, and then cooled to 550~600 °C and held for 90 min for carbon dioxide adsorption. During adsorption, the concentration of CO2 in the atmosphere is controlled at 10~20%, the flow rate is 80~120 ml / min, and the pressure is 1 atmosphere.

[0024] After the titanium-modified lithium silicate composite material obtained in this invention adsorbs carbon dioxide, it is heated to 850 ℃ and held for 20 min for desorption. During desorption, the atmosphere is controlled as pure N2, the gas flow rate is 100 mL / min, and the gas pressure is 1 atmosphere.

[0025] The adsorption and desorption temperatures of the products obtained by this invention are significantly lower than those of existing technologies.

[0026] The titanium-modified lithium silicate composite material designed and prepared in this invention, after optimization, has an initial carbon dioxide capture capacity of 0.17 g CO2 / g adsorbent, and after 20 cycles, the carbon dioxide capture capacity is 0.15 g CO2 / g adsorbent, with a cycle retention rate greater than 88%, such as 88.2%.

[0027] Beneficial effects of the embodiments of the present invention

[0028] 1. The titanium-modified lithium silicate composite material designed and prepared in this invention is the first to use a lithium source composed of lithium carbonate and lithium hydroxide to prepare highly active Li4SiO4, and innovatively introduces Li2TiO3 as a structural support material for the highly active Li4SiO4. After optimization, the composite material with the best performance was obtained, with an initial carbon dioxide capture capacity of 0.17 g CO2 / g adsorbent. After 20 cycles, the carbon dioxide capture capacity can still reach 0.15 g CO2 / g adsorbent, with a cycle retention rate of 88.2%.

[0029] 2. This invention has low equipment requirements, low energy consumption, simple steps, high controllability, and is easy to industrialize. Attached Figure Description

[0030] Figure 1 The image shows the XRD pattern of the pure Li4SiO4 material prepared in Example 1.

[0031] Figure 2 The image shows the XRD pattern of the Li4SiO4-20%H material prepared in Example 2.

[0032] Figure 3 The image shows the XRD pattern of the Li4SiO4-20%H-Ti composite material prepared in Example 3.

[0033] Figure 4 The graph shows the carbon dioxide capture performance of the pure Li4SiO4 material in Performance Test Example 1.

[0034] Figure 5 The graph shows the carbon dioxide capture performance of the Li4SiO4-20%H material in performance testing example 2.

[0035] Figure 6 The graph shows the carbon dioxide capture performance of the Li4SiO4-20%H-Ti composite material in performance testing example 3.

[0036] Figure 7 The graph shows the carbon dioxide capture performance of the pure Li4SiO4 material in performance testing example 4.

[0037] Figure 8 The graph shows the carbon dioxide capture performance of the Li4SiO4-20%H material in performance testing example 5.

[0038] Figure 9 The graph shows the carbon dioxide capture performance of the Li4SiO4-20%H-Ti composite material in performance testing example 6.

[0039] Figure 10 This is a scanning electron microscope image of the Li4SiO4-20%H-Ti composite material prepared in Example 3. Detailed Implementation

[0040] One embodiment of the present invention provides a titanium-modified lithium silicate composite material, comprising Li4SiO4 and Li2TiO3. The highly active Li4SiO4 material, prepared from a binary lithium source composed of lithium carbonate and lithium hydroxide, is used for carbon dioxide capture, while Li2TiO3 serves as a structural support material for Li4SiO4, further enhancing the stability of the material during repeated carbon dioxide capture. This effectively overcomes the technical shortcomings of traditional lithium silicate, such as low capacity and poor cycle stability. Another embodiment of the present invention provides a method for preparing the aforementioned titanium-modified lithium silicate composite material.

[0041] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with specific embodiments.

[0042] Example 1

[0043] This example provides a method for preparing pure Li4SiO4 material, including the following steps:

[0044] S1: Lithium carbonate and silicon dioxide were ball-milled and mixed, then sintered at high temperature in a tube furnace to obtain pure Li4SiO4 material. Figure 1 The image shows the XRD pattern of pure Li4SiO4 material.

[0045] The mass ratio of lithium carbonate to silicon dioxide in S1 is 8.3:1.7.

[0046] The ball milling conditions described in S1 are 800 r / min, ball milling time of 6 h, and ball-to-material mass ratio of 8:1.

[0047] The sintering temperature described in S1 is 900 ℃, and the sintering program is 0-500 ℃, 5 ℃ / min, 500-800 ℃, 10 ℃ / min, 800-900 ℃, 5 ℃ / min, and holding for 2 h.

[0048] Example 2

[0049] This example provides a method for preparing highly active Li4SiO4 materials, including the following steps:

[0050] S1: A binary lithium source precursor composed of commercial lithium carbonate and lithium hydroxide (the mass ratio of commercial lithium carbonate to lithium hydroxide is 8:2) is ball-milled and mixed evenly with silica, and then sintered at high temperature in a tube furnace to obtain a highly active Li4SiO4 material, denoted as Li4SiO4-20%H. Figure 2 The image shows the XRD pattern of Li4SiO4-20%H material.

[0051] In step S1, the binary lithium source precursor composed of lithium carbonate and lithium hydroxide has a mass ratio of lithium carbonate to lithium hydroxide of 8:2.

[0052] In step S1, the mass ratio of the binary lithium source precursor to silicon dioxide is 6.9:3.1.

[0053] In step S1, the ball milling conditions and high-temperature sintering conditions are the same as in Example 1.

[0054] Example 3

[0055] This example provides a method for preparing titanium-modified lithium silicate composite materials, including the following steps:

[0056] S1: A binary lithium source precursor composed of commercial lithium carbonate and lithium hydroxide (mass ratio of commercial lithium carbonate to lithium hydroxide is 8:2), SiO2 and TiO2 (mass ratio of binary lithium source precursor, SiO2, and TiO2 is 6:2:2) were ball-milled and mixed evenly. The mixture was then sintered at high temperature in a tube furnace to obtain a titanium-modified lithium silicate composite material, denoted as Li4SiO4-20%H-Ti. Figure 3 The image shows the XRD pattern of the Li4SiO4-20%H-Ti material.

[0057] In step S1, the component ratio, ball milling conditions, and high-temperature sintering conditions of the binary lithium source precursor composed of lithium carbonate and lithium hydroxide are the same as in Example 2; in step S1, the mass ratio of Li4SiO4 and Li2TiO3 finally obtained from the binary lithium source precursor, SiO2 and TiO2 is 8:2.

[0058] Example 4

[0059] This example provides a method for testing the CO2 recycling performance of a product, including the following steps:

[0060] S1: Weigh approximately 10 mg of the products obtained in step S1 of Examples 1, 2, 3, and 6, and place them in a platinum crucible.

[0061] S2: The test procedure was designed to heat the room temperature to 850 ℃, hold it at that temperature for 5 min, and then activate it without introducing carbon dioxide.

[0062] S3: The adsorption program is designed as follows: cool to 600 ℃ and hold for 90 min. The concentration of CO2 in the controlled atmosphere is 15%, the flow rate is 100 ml / min, and the pressure is 1 atmosphere.

[0063] S4: After completing S3, execute the desorption procedure by heating to 850 ℃ and holding for 20 min to perform desorption. The controlled atmosphere is pure N2, the gas flow rate is 100 mL / min, and the gas pressure is 1 atmosphere.

[0064] S5: Repeat steps S3 and S4 sequentially for a total of 20 cycles to complete the material CO2 cyclic capture performance test.

[0065] Example 5

[0066] This example provides a method for testing the product's CO2 low-temperature cycling capture performance, including the following steps:

[0067] S1: Weigh approximately 10 mg of the products obtained in step S1 of Examples 1, 2, 3, and 6, and place them in a platinum crucible.

[0068] S2: The test procedure was designed to heat the room temperature to 850 ℃, hold it at that temperature for 5 min, and then activate it without introducing carbon dioxide.

[0069] S3: The adsorption program is designed as follows: cool to 550 ℃ and hold for 90 min. The concentration of CO2 in the controlled atmosphere is 15%, the flow rate is 100 ml / min, and the pressure is 1 atmosphere.

[0070] S4: After completing S3, execute the desorption procedure by heating to 850 ℃ and holding for 20 min to perform desorption. The controlled atmosphere is pure N2, the gas flow rate is 100 mL / min, and the gas pressure is 1 atmosphere.

[0071] S5: Repeat steps S3 and S4 sequentially for a total of 10 cycles to complete the low-temperature CO2 cyclic capture performance test of the material.

[0072] Example 6

[0073] This example provides the performance of a titanium-modified adsorbent prepared by directly mixing two phases, Li4SiO4 and Li2TiO3 (mass ratio 8:2, non-in-situ generation). The CO2 capture performance of this material was tested according to the test method in Example 4. The initial CO2 capture capacity of the prepared adsorbent was approximately 0.13 g CO2 / g adsorbent, and after 20 cycles, the CO2 capture capacity was approximately 0.09 g CO2 / g adsorbent.

[0074] Performance Testing Example 1

[0075] Weigh 10.23 mg of pure Li4SiO4 material (precursor lithium carbonate) obtained in step S1 of Example 1, place it in a platinum crucible adapted to a thermogravimetric analyzer, and test the CO2 capture performance of the pure Li4SiO4 material according to the test method of Example 4.

[0076] like Figure 4 As shown, the carbon dioxide capture capacity of pure Li4SiO4 remained at around 0.05 g CO2 / g adsorbent throughout 20 cycles, indicating that the overall carbon dioxide adsorption capacity of pure Li4SiO4 was at an extremely low level.

[0077] Performance Testing Example 2

[0078] 9.89 mg of the Li4SiO4-20%H material (composed of lithium carbonate and lithium hydroxide precursors in a mass ratio of 8:2) prepared in step S1 of Example 2 was weighed and placed in a platinum crucible compatible with a thermogravimetric analyzer. The CO2 capture performance of the high-activity Li4SiO4 material was tested according to the test method of Example 4.

[0079] The cycling performance of Li4SiO4-20%H material is as follows: Figure 5 As shown, the initial carbon dioxide capture capacity of the Li4SiO4-20%H material was 0.12 g CO2 / g adsorbent. After 20 cycles, the carbon dioxide capture capacity was 0.09 g CO2 / g adsorbent, with a cycle retention rate of 75.0%. It can be seen that the highly active Li4SiO4 prepared using a binary lithium source composed of lithium carbonate and lithium hydroxide exhibits a significantly improved carbon dioxide capture capacity compared to pure Li4SiO4 material under the same conditions, but there is still room for improvement in cycle stability.

[0080] Performance Testing Example 3

[0081] Weigh 10.01 mg of the Li4SiO4-20%H-Ti composite material prepared in step S1 of Example 3 (the mass ratio of lithium silicate to lithium titanate was 8:2), place it in a platinum crucible adapted to a thermogravimetric analyzer, and test the CO2 capture performance of the composite material according to the test method of Example 4.

[0082] The cycling performance of Li4SiO4-20%H-Ti material is as follows: Figure 6 As shown, the initial carbon dioxide capture capacity of the Li4SiO4-20%H-Ti composite material was 0.17 g CO2 / g adsorbent. After 20 cycles, the carbon dioxide capture capacity was 0.15 g CO2 / g adsorbent, with a cycle retention rate of 88.2%. It can be seen that the carbon dioxide capture capacity of the Li4SiO4-20%H-Ti composite material prepared by ball milling and sintering in this embodiment of the invention is significantly improved compared to pure Li4SiO4 material under the same conditions. Furthermore, compared to Li4SiO4-20%H material, the adsorption capacity and cycle stability are further improved.

[0083] Performance Testing Example 4

[0084] Weigh 10.11 mg of pure Li4SiO4 material (precursor lithium carbonate) obtained in step S1 of Example 1, place it in a platinum crucible adapted to a thermogravimetric analyzer, and test the CO2 capture performance of the pure Li4SiO4 material under low-temperature adsorption conditions according to the test method of Example 5.

[0085] like Figure 7 As shown, the initial carbon dioxide capture capacity of pure Li4SiO4 material was 0.042 g CO2 / g adsorbent. After 10 cycles, the carbon dioxide capture capacity was 0.025 g CO2 / g adsorbent, with a cycle retention rate of 59.5%. It can be seen that as the adsorption temperature decreases, the carbon dioxide capture performance of pure Li4SiO4 further decreases, reaching an extremely low level.

[0086] Performance Testing Example 5

[0087] Weigh 9.98 mg of the Li4SiO4-20%H material (composed of lithium carbonate and lithium hydroxide precursors in a mass ratio of 8:2) obtained in step S1 of Example 2, place it in a platinum crucible compatible with a thermogravimetric analyzer, and test the CO2 capture performance of the high-activity Li4SiO4 material under low-temperature adsorption conditions according to the test method of Example 5.

[0088] The cycling performance of Li4SiO4-20%H material is as follows: Figure 8As shown, the initial carbon dioxide capture capacity of the Li4SiO4-20%H material was 0.081 g CO2 / g adsorbent. After 10 cycles, the carbon dioxide capture capacity was 0.066 g CO2 / g adsorbent, with a cycle retention rate of 81.5%. This indicates that the highly active Li4SiO4 prepared using a binary lithium source composed of lithium carbonate and lithium hydroxide still achieves a significant improvement in carbon dioxide capture capacity compared to pure Li4SiO4 under the same conditions. Furthermore, although the performance fluctuation of the highly active Li4SiO4 prepared using the binary lithium source is relatively small as the adsorption temperature decreases, there is still room for improvement in cycle stability.

[0089] Performance Testing Example 6

[0090] 9.86 mg of the Li4SiO4-20%H-Ti composite material prepared in step S1 of Example 3 (the mass ratio of lithium silicate to lithium titanate was 8:2) was weighed and placed in a platinum crucible adapted to a thermogravimetric analyzer. The CO2 capture performance of the composite material was tested according to the test method of Example 5.

[0091] The cycling performance of Li4SiO4-20%H-Ti material is as follows: Figure 9 As shown, the initial carbon dioxide capture capacity of the Li4SiO4-20%H-Ti composite material was 0.11 g CO2 / g adsorbent. After 20 cycles, the carbon dioxide capture capacity was 0.10 g CO2 / g adsorbent, with a cycle retention rate of 90.9%. It can be seen that although the carbon dioxide capture capacity of the Li4SiO4-20%H-Ti composite material prepared by ball milling and sintering in the embodiments of this invention is significantly improved compared to pure Li4SiO4 material under the same conditions, the adsorption capacity and cycle stability are also further improved compared to Li4SiO4-20%H material, even with decreasing adsorption temperature.

[0092] A highly active Li4SiO4 matrix was synthesized using a binary lithium source composed of lithium carbonate and lithium hydroxide to enhance the intrinsic adsorption activity of the material. Based on this, Li2TiO3 was introduced in situ as a structural support material for Li4SiO4, significantly improving the stability of the material during repeated carbon dioxide capture. The prepared Li4SiO4-20%H-Ti composite material exhibited excellent CO2 capture performance. The initial CO2 capture capacity of the Li4SiO4-20%H-Ti composite material was 0.17 g CO2 / g adsorbent, and after 20 cycles, the CO2 capture capacity was 0.15 g CO2 / g adsorbent, with a cycle retention rate of 88.2%.

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A titanium-modified lithium silicate composite material, characterized in that: The composite material includes Li4SiO4 and Li2TiO3; the composite material is obtained by calcining a mixture of Li4SiO4 precursor, SiO2 and TiO2; the mass ratio of Li4SiO4 to Li2TiO3 in the composite material is 7-9:1-3; the Li4SiO4 precursor is composed of lithium carbonate and lithium hydroxide in a mass ratio of lithium carbonate:lithium hydroxide = 7.8-8.2:1.8-2.2; and the calcination temperature is 700-950 ℃.

2. The titanium-modified lithium silicate composite material according to claim 1, characterized in that: The mass ratio of lithium carbonate to lithium hydroxide is 8:

2.

3. The titanium-modified lithium silicate composite material according to claim 1, characterized in that: The particle size of the rutile phase TiO2 used is less than or equal to 20 nm.

4. The titanium-modified lithium silicate composite material according to claim 1, characterized in that: The particle size of the SiO2 used is less than or equal to 50 nm.

5. The titanium-modified lithium silicate composite material according to claim 1, characterized in that: The calcination time is 1-3 hours.

6. The titanium-modified lithium silicate composite material according to claim 1, characterized in that: The calcination temperature is 820-900 ℃.

7. A method for preparing the titanium-modified lithium silicate composite material according to any one of claims 1-5, characterized in that, Includes the following steps: The raw materials are weighed according to the target group ratio, then mixed evenly, and calcined at 700-950 ℃ to obtain the composite material; the raw materials include Li4SiO4 precursor, SiO2 and TiO2.

8. The method for preparing a titanium-modified lithium silicate composite material according to claim 7, characterized in that: The mixture is homogenized by ball milling, with the milling speed controlled at 600-800 r / min and the milling time at 4-8 h.

9. The method for preparing a titanium-modified lithium silicate composite material according to claim 7, characterized in that: The Li2TiO3 used was obtained by in-situ sintering Li4SiO4 and TiO2 at high temperature; the high temperature sintering temperature was 820-900℃. In the composite material, the mass ratio of Li4SiO4 to Li2TiO3 is 7-9:1-3; preferably 7.5-8.5:1.5-2.

5.

10. The method for preparing a titanium-modified lithium silicate composite material according to claim 9, characterized in that: The obtained titanium-modified lithium silicate composite material had an initial carbon dioxide capture capacity of 0.17 g CO2 / g adsorbent, and after 20 cycles, the CO2 capture capacity was 0.15 g CO2 / g adsorbent, with a cycle retention rate of 88.2%.